Visual perception of urban greening in public parks: evidence from Trabzon City, Turkey - Guneroglu, Nilgun; Bekar, Makbulenur (Journal of Environmental Engineering and Landscape Management, 2022)
Urban parks are of the most important components of green infrastructure in cities. Number and size of green areas decrease especially due to increase in population and urbanization. Urban parks rank first among green areas that increase and improve the quality of life in cities. Urban parks are places where people can commune with nature and spend their free time for leisure. Accessibility of urban parks, their recreational facilities and space identity are very effective on satisfaction of users. This study is about EYOF Park in Trabzon city. Visual perception analysis carried out using landscape quality criteria. User satisfaction was analyzed with statistical analyses. As a result of analysis, the highest correlations were found between “color” and “texture” (r = 0.790). The most important reasons of park visit was found to be for “relaxing” purposes, moreover “lack of car park” was stated as the most important problem for the park.